Distribution and abundance of the lionfish Pterois volitans (Scorpaeniformes: Scorpaenidae) and associated native species in Parque Marino Cayos de San Felipe, Cuba - de la Guardia, Elena; Cobián Rojas, Dorka; Espinosa, Leonardo; Hernández, Zaimiuri; García, Lázaro; Arias González, Jesús Ernesto (Revista de Biología Tropical, 2017)
The first lionfish sighting at the National Park "Cayos de San Felipe" was in 2009 and could be a threat to its marine ecosystem diversity and their capacity to generate services. To analyze the incidence of the lionfish invasion in the area, an annual sampling was conducted between 2013 and 2015. Lionfish abundance and size was investigated on mangroves through visual census on ten transects of 30x2 m/station, and on coral reefs (15 and 25 m deep) with stereo video on six transects of 50x2 m/station. Additionally, incidence of potential native competitors and predators on coral reefs were also estimated. Over the three years, the average density of lionfish varied between 0.0-1.3 indiv./100 m2 per sample stations and it was not significantly different among habitats (mangroves with 0.6 indiv./100 m2, reefs at 15 m - 0.4 indiv./100 m2 and reef at 25 m with 0.3 indiv./100 m2). Lionfish’s density was equal to or lower than competitors’ density, and was equal to or higher than predator’s density in both depths. While lionfish density on mangroves and on reefs at 25 m remained temporally stable, it decreased on reefs at 15 m. Temporary increase in the competitor’s density was observed and the predator´s density did not change during the monitored time. Lionfish size varied between 5 and 39 cm; the average fish size from mangroves (12.6 cm) was consistently lower than from reefs (25.2 cm) and showed no variations among years. Lionfish size in reefs was higher than competitor’s size and lower than that of predator. Results showed that in the park: 1) mangroves represent lionfish nursery areas; 2) incidence of reef lionfish was not as high as in other areas of Cuba and the Caribbean; and 3) lionfish abundance in reefs tended to decrease over the years, without the intervention of extractive activities or high abundance of large size native groupers. In this sense, recommendations are made to continue monitoring and to investigate lionfish effects and factors that are regulating its incidence in the park.